China-US tech war: the impact on global food security - Zhang, Hongzhou (2023)
Emerging technologies could potentially revolutionise agriculture. However, the China-US tech war and systemic US-China competition, already expanding into agricultural technologies (agritech), present both opportunities and challenges for global food security. This could result in unequal access to agritech globally, particularly for emerging countries, thus bringing about serious consequences for global food security.